ZnO nanorod-coated tapered plastic fiber sensors for relative humidity - Zuraidah*, Harith; Malathy*, Batumalay; Ninik, Irawati; Sulaiman Wadi, Harun; Harith, Ahmad; Hu, Taoping (Elsevier, 2020)
Monitoring humidity has becoming an important issue in various areas of applications such as instrumentation, automated systems, climatology, and agriculture A simple relative humidity sensor is proposed by employing tapered plastic optical fiber (POF) coated with ZnO nanorods that were grown using hydrothermal method. The tapering of the POF is done using chemical etching method. To enhance the performance of a POF as sensor, a certain length of the fiber needs to be tapered. The total amount of evanescent wave increases with increasing reflections of light with the sample in tapered fibers. The measurement of the proposed sensor is based on the modulation of light intensity, recorded at various humidity level with a lock-in amplifier. It is observed that the proposed sensor exhibited a sensitivity and slope of linearity of 0.0295 %/mV and of 98.38 % with limit of detection 0.7133%. ZnO nanorods has a high surface to volume ratio which allows the rods to absorb more water that consequently changes its refractive index (RI)and the modulation of light propagating through the fiber. The humidity sensitive layer of the ZnO nanorods has an RI value which is higher than that of the core creates a lossy waveguide which leads to decrease in output voltage. The output power change in the proposed sensor is based on the interaction of the evanescent field in tapered POF with the external medium. When compared to the previous method used in growing ZnO, which is the sol–gel method, hydrothermal method has shown an enhancement in both the sensitivity and linearity. The field emission scanning electron microscopy (FESEM) proved the successful coating of ZnO into the POF, which contributed to the increase in the performance of the sensor.